TINJAUAN TENTANG MANAJEMEN PERWASITAN DI ASOSIASI FUTSAL PROVINSI (AFP) NUSA TENGGARA TIMUR - Babang, Veramyta Maria Martha Flora; Margiani, Kristin; Palaialu, Yerobeam (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
The formulation of the problem in this research is how to organize refereeing in the East Nusa Tenggara Province Futsal Association and how the implementation carried out by the East of Nusa Tenggara Province Futsal Association in terms of planning, This research aims to find out how to organize refereeing in the East Nusa Tenggara Province Futsal Association and also to know how the implementation of the East Nusa Tenggara Province Futsal Association in terms of planning, implementation and supervision of refereeing, especially in Kupang city. This study uses a qualitative descriptive method. The results of this study indicate that (1) the organizational structure of the East Nusa Tenggara Provincial Futsal Association (AFP) is generally very good. (2) The development of refereeing futsal association estabilish since 2016 until now can be said to have developed very significantly, this can be chosen from the beginning of the formation of an association that did not have a licensed referee but until this time the East Nusa Tenggara Province Futsal Association was a complete failure. Approximately one hundred referees have national level III refereeing licenses and thirty National Lenvel referees in East Nusa Tenggara. (3) Planning management carried out by the East Nusa Tenggara Provincial Futsal Association (AFP) is planning to support futsal coaching through a licensed futsal referee. it can be seen how the association tries to emphasize referees in East Nusa Tenggara Province with various rules so that the referees can run according to the direction of the organization.